The Urgency of Proverbs-Based Childhood Education Facing the Era of Society 5.0: Efforts to Realise A Harmonious Christian Family - Imeldawati, Tiur; Panjaitan, Binur; Marbun, Rencan C. (LPPM IAKN Tarutung, 2024)
This research aims to explain the concept of child education based on the book of Proverbs in facing the era of society 5.0 where the challenges in educating children are increasingly complex and need to be addressed properly by parents. The research questions formulated are how is the concept of child education based on the book of Proverbs and how does child education based on the book of Proverbs face educational challenges in the era of society 5.0? This research uses a qualitative method with a descriptive approach in which the researcher examines the book of Proverbs by examining texts related to the topic of discussion and conducting a word study of several parts of the related text. The results of this study are useful both theoretically and practically. The novelty of this research is a comprehensive study related to child education in the book of Proverbs facing the era of society 5.0. Whereas previous studies focused more on one passage or one verse of Proverbs without linking it to the era of society 5.0 and in other sections there were studies of the era of society 5.0 but were not accompanied by biblical foundations only limited to general studies. The study presented can be used as reference material for future researchers.